Sustainable Biofuel Production from Animal Manure and Crop Residues in Ghana - Patience Afi Seglah; Yajing Wang; Hongyan Wang; Chunyu Gao; Yuyun Bi (Energies, 2022)
Renewable energy is predicted to play a crucial role in the energy sector as transitioning from fossil fuels to biofuels is key to achieving carbon neutrality. The comprehensive utilization of livestock manure and crop residues as a viable source of biofuels can play a significant role in Ghana’s future energy system. This current study aims to examine and predict the biofuel potential in Ghana from animal manure and crop residues. The biogas-biomethane potential of animal manure is determined using anaerobic digestion technology, whereas crop residues’ bioethanol potential is assessed using computational and analytical approaches. The findings demonstrate that animal manure biogas potential is 237.72 normal million cubic meters (NMm3). The highest manure-biogas potential per animal is from cattle (27.15 Nm3) and pigs (18.15 Nm3), while the least contribution is from chickens (1.80 Nm3). In addition, the annual bioethanol production is 3.74 gigaliters (GL), and residues from maize (0.88 GL), yams (0.82 GL), and plantains (0.47 GL) had the largest share per annum. By 2100, Ghana has the potential to produce 1288.56 NMm3 of manure-based biogas which can offset 13.88% of liquefied petroleum gas (LPG) consumption. The biogas potential positively correlates with the biomethane potential of 901.99 NMm3. Furthermore, 91.85% of the 14.76 GL of bioethanol will be from food crop residues. This study provides critical information to lawmakers and energy planners with strategies to achieve energy security and minimize the ecological footprint in an optimistic scenario.